At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Which equation is equivalent to the given equation?

-4(x-5) + 8x = 9x - 3

A. 5x = -12
B. -5x = -23
C. -5x = 2
D. 5x = 17


Sagot :

To determine which equation is equivalent to the given equation:

[tex]\[ -4(x-5) + 8x = 9x - 3 \][/tex]

we should follow a series of algebraic steps. Let’s go through them methodically:

1. Distribute the [tex]\(-4\)[/tex] on the left side of the equation:
[tex]\[ -4(x-5) + 8x = 9x - 3 \][/tex]
[tex]\[ -4x + 20 + 8x = 9x - 3 \][/tex]

2. Combine like terms on the left side:
[tex]\[ (-4x + 8x) + 20 = 9x - 3 \][/tex]
[tex]\[ 4x + 20 = 9x - 3 \][/tex]

3. Isolate the [tex]\(x\)[/tex] terms on one side and the constants on the other. We'll move the [tex]\(9x\)[/tex] term from the right to the left:
[tex]\[ 4x - 9x + 20 = -3 \][/tex]
[tex]\[ -5x + 20 = -3 \][/tex]

4. Isolate the [tex]\(x\)[/tex] term by moving the constants to the other side:
[tex]\[ -5x = -3 - 20 \][/tex]
[tex]\[ -5x = -23 \][/tex]

Hence, the equation equivalent to the given equation is:
[tex]\[ -5x = -23 \][/tex]

This matches choice B. Therefore, the correct answer is:

[tex]\[ \boxed{B. \, -5x = -23} \][/tex]